Risk of Neonatal Sepsis with Rescue Steroids in Preterm Premature Rupture of Membranes versus Intact Membranes [25F]. (May 2018) - TenBrink, Emily E.; Quain, Angela; Daggy, Joanne; Haas, David Michael; Shanks, Anthony
Abstract : INTRODUCTION: Currently there is insufficient evidence to make a recommendation for rescue steroids in women with preterm premature rupture of membranes (PPROM). Prior studies have suggested an increased risk of neonatal sepsis and studies investigating rescue steroids excluded these patients. The objective of our study was to compare the rate of neonatal sepsis after rescue steroids in women with PPROM compared to intact membranes. METHODS: We performed a retrospective cohort study of singleton gestations 23.0 to 34.0 weeks, who received rescue corticosteroids at our institution between January 2009 and October 2016. Patients were separated into three groups based on membrane status at the time of corticosteroid administration; Group 1 (intact at initial course/intact at rescue course), Group 2 (intact at initial course/PPROM at rescue course), and Group 3 (PPROM at initial course/PPROM at rescue course). The primary outcome, neonatal sepsis, was compared between the three groups. Patient characteristics and neonatal outcomes were analyzed with Fisher's exact test and Anova. RESULTS: 143 women were eligible. Neonatal sepsis occurred in 6.8% (7/103) of patients in Group 1, 21.1% (4/19) of patients in Group 2, and 23.8% (5/21) of patients in Group 3 (p 0.021). The relative risk of neonatal sepsis after a rescue course of steroids was 3.31 (95% CI= [1.32, 8.29]) for patients with PPROM (Group 2 and Group 3) compared to those with all intact membranes (Group 1). CONCLUSION: A rescue course of corticosteroids in PPROM was associated with an increased rate of neonatal sepsis. Larger studies are needed to further investigate this association.